Doorbell monitoring system using ESP32-CAM based on Internet of Things (IoT) - Zakaria, Rahman; Dewi, Citra; Hastuti; Ranuharja, Fadli (Department of Electrical Engineering Universitas Negeri Padang, 2024)
One use of internet of things (IoT) technology is in remote monitoring systems, for example home monitoring systems. One medium that can be used to control an IoT system is a messaging application. In this research, a doorbell monitoring system using IoT-based ESP32-CAM was designed by connecting the doorbell with the ESP32-CAM. ESP32-CAM is used as a microcontroller that connects all devices. The advantage of the ESP32-CAM is that it has Wi-Fi, Bluetooth, a secure digital (SD) card module, and a camera that is directly embedded on the board. The doorbell and ESP32-CAM are connected to each other with the door lock solenoid and power supply. To operate the tool, a Telegram messaging application is used using Telegram's bot. Telegram bots can be accessed with a bot ID and bot token created using BotFather. This system has no noise when the doorbell is pressed. The ESP32-CAM camera can take good quality images and testing on the chat bot went well. The door lock solenoid can work according to commands in the Telegram chat bot and all commands have been tested and provide information in the form of chat in the form of text and images. The research results of this system allow homeowners to see and monitor guests via smartphone in real-time with a time range of 3 to 6 seconds